Smart disclosure: an enabler for multinationals to reduce human rights violations in global supply chains - Wang, Stephanie Lu; Lee, Yejee; Li, Dan (Journal of International Business Studies, 2024)
Existing research has underscored that the lack of supplier visibility poses a primary obstacle for multinational corporations (MNCs) to tackle human rights violations within their global supply chains (GSC). To address this challenge, MNCs are increasingly adopting the concept of “smart disclosure” to enhance supplier visibility. However, its conceptualization, operationalization, and efficacy in reducing human rights violations, remain unclear. Filling this gap, we first draw on research about attributes of digital technologies and information disclosure to define and operationalize smart disclosure in the context of GSC. We then draw on insights from institutional theory to theorize that smart disclosure – as a visibility-enhancing mechanism – enables MNCs to fulfill the role of “institutional carriers” and effectively impose institutional pressures on suppliers, fostering an environment where suppliers’ adherence to human rights standards is desired, supported, and rewarded. We further propose that this effect is stronger for suppliers with higher centrality in GSC networks and those in countries with greater civil society development. We found support for our arguments by analyzing 8527 observations at the MNC-supplier-year level in the global apparel industry from 2014 to 2020.